2019
DOI: 10.7600/jpfsm.8.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-citrulline intake on intermittent short-time high-intensity exercise performance in male collegiate track athletes

Abstract: Enhanced exercise performance and anti-fatigue effects following L-citrulline (Cit) intake have been reported in resistance training and endurance exercise, but not in intermittent short-time high-intensity exercise. Therefore, the effect of Cit intake on intermittent short-time high-intensity exercise performance in collegiate athletes was investigated. A double-blind, placebo-controlled crossover trial was performed using nine male collegiate track athletes (age 20.9 ± 1.6 years). Each participant ingeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Our findings showed that there was no difference in BLa before or after TTs between groups, which is consistent with previous studies [20,32,33]. In the study of Terasawa et al [3], for both the L-Cit and Pla groups, the amount of NOx, on day 7, at the time of post-exercise significantly increased compared to pre-exercise while there was no difference on day 0 [3]. While we observed no change in BLa after high-intensity exercise with L-Cit supplementation in this study, previous animal studies have reported lower post exercise BLa and ammonia concentration [46], as well as a lower rate of muscle PCr reduction [47] with L-Cit.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that there was no difference in BLa before or after TTs between groups, which is consistent with previous studies [20,32,33]. In the study of Terasawa et al [3], for both the L-Cit and Pla groups, the amount of NOx, on day 7, at the time of post-exercise significantly increased compared to pre-exercise while there was no difference on day 0 [3]. While we observed no change in BLa after high-intensity exercise with L-Cit supplementation in this study, previous animal studies have reported lower post exercise BLa and ammonia concentration [46], as well as a lower rate of muscle PCr reduction [47] with L-Cit.…”
Section: Discussionsupporting
confidence: 93%
“…Nitric oxide (NO) is an important physiological signalling molecule for skeletal muscle perfusion, metabolism, contractility, and fatigue resistance [1,2], and it is attracting much interest in sport physiology and nutrition as an ergogenic aid [3]. To date, many studies have shown that dietary NO related supplements, such as nitrate-rich beetroot juice or watermelon juice, enhance athletic performance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation of an appropriate sample size was conducted using the G*Power analysis software (25) . Our rationale for sample size was based on a previous study evaluating changes in blood NOx responses to high-intensity exercise after acute L-Cit supplementation in nine young men (18,26) . This study revealed an effect size of 0•4 for the increase in NOx after high-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Stanelle et al (13) reported that L-Cit supplementation might lead to a slight improvement in the cycling performance of trained athletes. It was also shown that, due to exercise-induced muscle damage, L-Cit supplementation can decrease serum creatine kinase concentrations along with increasing perceived recovery (13,18) . According to prior research, L-Cit supplementation reduces concentrations of lactate and muscle pain 24 h after exercise (13,16) , which might be related to its antioxidant effects.…”
mentioning
confidence: 99%